Application of Monte Carlo Simulation for Analysis of Costs and Economic Risks in a Banking Agency - Silva, Saulo Andre; Abreu, Pedro Henrique Camargo de; Amorim, Fernando Rodrigues de; Santos, David Ferreira Lopes [UNESP] (Ieee-inst Electrical Electronics Engineers Inc, 2019)
Through an observation of the increasingly globalized scenario in which the markets are inserted, it is evident the direct impact on competitiveness among companies combined with government incentives for the creation of new companies, fostering job creation and economic growth. However, this cycle ends up strengthening competition within the markets, and it is increasingly recurring the emergence of new technologies to reinforce Performance Management on business processes. Therefore, the present work has the objective of investigate the importance of planning and managing risks in business structure results, analyzing the economic risk factors of a banking agency located in the State of Sao Paulo. Thus, the Monte Carlo Simulation was applied, which operates statistically in the likelihood of occurrence of certain scenarios, will be applied, allowing the institution to strengthen its risk management by creating contingency plans for the scenarios analyzed. Regarding the results obtained, in all simulations with controlled losses and without any anomalies in the market, the positive results outweigh the negative, and the profit averages were higher compared with the period raised (simulation input).
Keywords: Monte Carlo methods; Economics; Computational modeling; Software; IEEE transactions; Banking; Companies; Banking sector; Monte Carlo Method; Project management; Stochastic modeling